MEASURE OF NONCOMPACTNESS IN THE STUDY OF SOLUTIONS FOR A SYSTEM OF INTEGRAL EQUATIONS - Karakaya, Vatan; Mursaleen, Mohammad; Bouzara, Nour El Houda; Sekman, Derya (INDONESIAN MATHEMATICAL SOC, 2019)
In this work, we prove the existence of solutions for a tripled system of integral equations using some new results of fixed point theory associated with measure of noncompactness. These results extend the results in some previous works. Also, the condition under which the operator admits fixed points is more general than the others in literature.
Keywords: Measure of noncompactness; Fixed point; System of integral equations; KEELER CONDENSING OPERATORS; FIXED-POINT THEOREMS; EXISTENCE; Mathematics